BLEBERAN TOURIST VILLAGE OF GUNUNG KIDUL: COMPONENT ANALYSIS OF ITS ATTRACTION, PRODUCT, MANAGEMENT AND MARKETING - Marsono Marsono (Journal of Business on Hospitality and Tourism, 2016)
The need to live naturally with the principal of ‘going back to nature’ has resulted in development of new tourist attraction: the tourist village. Village potentials such as varied natural attractions, friendly local people, unspoiled natural setting and fresh air are among attractions for the tourists. This research is aimed primarily at revealing tourist attraction elements of the products, the management, the product itself and its marketing in Bleberan Tourist Village of Playen, Gunung Kidul Regency, Yogyakarta Special Region. The primary data cover all activities from its launching in 2009 to the end of 2015, in which its development could be seen clearly. The theoretical approach applied in this research is tourist attraction component theory on the product, its management and marketing.